Preparation method of waterproof gypsum plaster board based on desulfurized gypsum
By using materials such as desulfurization gypsum, modified fibers and modified starch in paper gypsum board, and combined with silicone waterproofing agent, the shortcomings of existing paper gypsum board in terms of mechanical strength and water absorption are solved, and a higher level of energy has been achieved. The strength and lower water absorption meet strict standards.
Patent Information
- Application Number
- CN202411596576.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-18
AI Technical Summary
Existing paper-surface gypsum boards have shortcomings in terms of mechanical strength and water absorption, and it is difficult to meet strict standards.
Using waterproof paper-surface gypsum board based on desulfurization gypsum, the desulfurization gypsum powder, modified polyvinyl alcohol fiber, modified corn starch and other materials are combined with silicone waterproofing agent to form a board core and combine it with waterproof surface protection paper. Specific preparation processes improve the mechanical strength of the sheet and reduce water absorption.
It significantly improves the mechanical strength of paper gypsum board and reduces water absorption, so that it can better meet the standard requirements and provide better building materials performance.
Smart Images

Figure BDA0005127072000000151
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of gypsum board materials, and in particular to a method for preparing a waterproof gypsum board based on desulfurized gypsum. Background Art
[0002] Gypsum board is a widely used building material. It is mainly made of building gypsum as raw material, and is processed into a board core by adding appropriate additives and fibers, and then made into a board with special face paper. Compared with traditional building materials such as cement, bricks, and blocks, gypsum board is light, soundproof, heat-insulating, easy to process, and convenient to construct. At present, gypsum board can be roughly divided into two categories: desulfurized gypsum board and natural gypsum board according to raw materials. Desulfurized gypsum is an industrial byproduct obtained by desulfurization and purification of flue gas generated by the combustion of sulfur-containing fuels. Desulfurized gypsum is a lightweight building sheet made by mixing desulfurized gypsum with other components into slurry, combining it with face paper, and drying it. Summary of the invention
[0003] The present invention provides a waterproof paper-faced gypsum board based on desulfurized gypsum, comprising a board core and a waterproof facing paper, wherein the board core is bonded to the facing paper, and the raw materials of the board core comprise: desulfurized gypsum powder, modified polyvinyl alcohol fiber, modified corn starch, DL-tartaric acid, sodium trimethyl phosphate, organic silicon waterproofing agent, calcium polynaphthalene sulfonate and water, wherein the preparation method of the modified polyvinyl alcohol fiber is:
[0004] (1) adding 3-(methacryloyloxy)propyltrimethoxysilane to an aqueous solution of ethanol, stirring and mixing under an ultrasonic environment for more than 30 minutes, and then adding glacial acetic acid to adjust the pH of the solution to 4-5 to obtain a pretreatment solution; adding polyvinyl alcohol fiber to the pretreatment solution, heating it to 75±5° C. in a water bath, and then stirring it at a constant temperature for more than 20 minutes, separating the solid and the liquid, washing the solid phase with deionized water for more than 3 times, and drying it at 60° C. for more than 1 hour to obtain a pretreated fiber;
[0005] (2) preparing a composite N,N-dimethylformamide solution of 2-methyl-2-acrylamide propanesulfonic acid and acrylamide; adding the pretreated fiber to N,N-dimethylformamide in a reactor, stirring and dispersing for more than 20 minutes under an ultrasonic environment to obtain a dispersion; then adding diisopropylbenzene peroxide to the dispersion under stirring, heating the dispersion to 125±3° C. in a water bath after the addition is completed, and then adding the composite N,N-dimethylformamide solution of 2-methyl-2-acrylamide propanesulfonic acid and acrylamide under stirring after the addition is completed, closing the reactor after the addition is completed, magnetically stirring at a constant temperature of 125±3° C. for more than 5 hours, and then naturally cooling to room temperature, opening the reactor, separating the solid and the liquid, washing the solid phase with deionized water for more than 3 times, and drying at 60° C. for more than 1 hour to obtain a primary modified fiber;
[0006] (3) preparing an aqueous solution of ethylenediamine; adding the once modified fiber to a dilute sodium hydroxide solution, stirring for 10 to 15 minutes, then adding epichlorohydrin to the solution under stirring, continuing to stir for more than 30 minutes after the addition is completed, then separating the solid from the liquid, washing the solid phase with deionized water for more than 3 times, then washing with ethanol for more than 3 times, drying at 60°C for more than 1 hour, adding the dried solid phase to the aqueous solution of ethylenediamine, heating to 50±5°C in a water bath, then stirring for more than 5 hours, separating the solid from the liquid, washing the solid phase with deionized water for more than 3 times, and drying at 60°C for more than 1 hour, and obtaining the modified polyvinyl alcohol fiber.
[0007] Furthermore, the preparation method of the modified corn starch is:
[0008] Step 1, preparing an aqueous solution of sodium carbonate, wherein the concentration of sodium carbonate in the aqueous solution of sodium carbonate is 100 g / L, and the solvent is water; then adding corn starch powder to the aqueous solution of sodium carbonate; the amount ratio of corn starch powder added to the aqueous solution of sodium carbonate is corn starch powder: aqueous solution of sodium carbonate = 2 g: 100 mL; after the addition is completed, stirring for 40 to 50 minutes, filtering, and drying the filter cake at 50° C. for more than 10 hours to obtain pretreated starch;
[0009] Step 2: Heat the maleic anhydride in a water bath to 80±3°C to keep it melted, then add the pretreated starch, the mixing mass ratio of the pretreated starch and maleic anhydride is pretreated starch: maleic anhydride = 1:5; stir at a constant temperature of 80±3°C for more than 3h, filter, wash the filter cake with dichloromethane for more than 3 times, and dry at 50°C for more than 10h to obtain the modified corn starch.
[0010] Furthermore, the raw materials of the board core are calculated by weight as follows: 100 parts of desulfurized gypsum powder, 5-8 parts of modified polyvinyl alcohol fiber, 0.8-1.5 parts of modified corn starch, 1-2 parts of DL-tartaric acid, 1-2 parts of trimethyl sodium phosphate, 5-8 parts of silicone waterproofing agent, 1-4 parts of calcium polynaphthalene sulfonate, and 60-65 parts of water.
[0011] Furthermore, the organic silicon waterproofing agent is methyl high hydrogen silicone oil.
[0012] Furthermore, in the step (1), the mass ratio of 3-(methacryloyloxy)propyltrimethoxysilane added to the aqueous solution of ethanol is 3-(methacryloyloxy)propyltrimethoxysilane: aqueous solution of ethanol = 1 to 2:100; wherein the mass percentage of ethanol in the aqueous solution of ethanol is 95%, and the rest is water; the mass ratio of polyvinyl alcohol fiber added to the pretreatment solution is polyvinyl alcohol fiber: pretreatment solution = 8 to 10:100.
[0013] Furthermore, in the step (2), in the composite N,N-dimethylformamide solution of 2-methyl-2-acrylamidepropanesulfonic acid and acrylamide, the mass percentage of 2-methyl-2-acrylamidepropanesulfonic acid is 6% to 8%, the mass percentage of acrylamide is 0.6% to 1%, and the solvent is N,N-dimethylformamide; the mass ratio of the pretreated fiber added to N,N-dimethylformamide is pretreated fiber:N,N-dimethylformamide=1:30; the mass ratio of the added mass of the composite N,N-dimethylformamide solution of dicumyl peroxide, 2-methyl-2-acrylamidepropanesulfonic acid and acrylamide to the mass ratio of the pretreated fiber in the dispersion is dicumyl peroxide: composite N,N-dimethylformamide solution of 2-methyl-2-acrylamidepropanesulfonic acid and acrylamide: pretreated fiber=0.1-0.2:10-15:1.
[0014] Furthermore, in the step (3), the concentration of ethylenediamine in the aqueous solution of ethylenediamine is 10-15 g / L, and the solvent is water; the primary modified fiber is added to the dilute sodium hydroxide solution in a ratio of primary modified fiber: dilute sodium hydroxide solution = 1 g: 50 mL, wherein the concentration of sodium hydroxide in the dilute sodium hydroxide solution is 8-10 g / L, and the solvent is water; the ratio of the mass of added epichlorohydrin to the mass of the primary modified fiber in the solution is epichlorohydrin: primary modified fiber = 4-6:1; the ratio of the amount of the dried solid phase added to the aqueous solution of ethylenediamine is the dried solid phase: aqueous solution of ethylenediamine = 1 g: 30 mL.
[0015] The present invention also discloses a method for preparing the waterproof gypsum board, which comprises the following steps:
[0016] 1) weighing each component according to the weight proportion, then uniformly mixing the modified polyvinyl alcohol fiber, DL-tartaric acid, sodium trimethyl phosphate, calcium polynaphthalene sulfonate and water, and then adding the remaining desulfurized gypsum powder, modified corn starch and organosilicon waterproofing agent after uniform mixing, and mixing and stirring to obtain slurry;
[0017] 2) Casting the slurry in a mold with front and rear waterproof facing papers, removing the mold after initial setting, drying at 160-170° C. for 30-40 min, then drying at 110-130° C. for 60-80 min; and then drying at 40-50° C. for more than 12 h to obtain the waterproof paper-faced gypsum board.
[0018] The beneficial effect of the present invention is that the gypsum board prepared by the method of the present invention has good mechanical strength and low water absorption, and can well meet the standard requirements. Comparative Example 2 and each comparative example show that by using the modification process of the present invention on the polyvinyl alcohol fiber, the strength of the gypsum board can be significantly improved and the water absorption rate can be improved. This is mainly due to: firstly, alkylation treatment is performed on the surface of the polyvinyl alcohol fiber, and then acrylamide groups are grafted to improve the dispersion of the fiber and the compatibility of the fiber with gypsum, reduce the pores between the phases, and improve the density; then the fiber surface is aminoated, and maleic anhydride modified starch is used to make the binding force between the modified fiber and the modified starch stronger, thereby improving the overall strength of the material. DETAILED DESCRIPTION
[0019] The present invention will be further described below in conjunction with the embodiments.
[0020] Example 1
[0021] A waterproof paper-faced gypsum board based on desulfurized gypsum comprises a board core and a waterproof face paper, wherein the board core is bonded to the face paper, and the raw materials of the board core comprise: desulfurized gypsum powder, modified polyvinyl alcohol fiber, modified corn starch, DL-tartaric acid, trimethyl sodium phosphate, silicone waterproofing agent, calcium polynaphthalene sulfonate and water, wherein the raw materials are calculated by weight as follows: 100 parts of desulfurized gypsum powder, 5 parts of modified polyvinyl alcohol fiber, 0.8 parts of modified corn starch, 1 part of DL-tartaric acid, 1 part of trimethyl sodium phosphate, 5 parts of silicone waterproofing agent (methyl high hydrogen silicone oil), 1 part of calcium polynaphthalene sulfonate and 60 parts of water; wherein the preparation method of the modified polyvinyl alcohol fiber is as follows:
[0022] (1) 3-(methacryloyloxy)propyltrimethoxysilane is added to an aqueous solution of ethanol, and the mass ratio of 3-(methacryloyloxy)propyltrimethoxysilane to the aqueous solution of ethanol is 3-(methacryloyloxy)propyltrimethoxysilane: ethanol aqueous solution = 1:100; the mass percentage of ethanol in the aqueous solution of ethanol is 95%, and the rest is water; stirring and mixing for 30 minutes under an ultrasonic environment, and then adding glacial acetic acid to adjust the pH of the solution to 4 to obtain a pretreatment solution; polyvinyl alcohol fiber (diameter 35-40 μm, length 9 mm, all the examples and comparative examples are from the same batch) is added to the pretreatment solution, and the mass ratio of polyvinyl alcohol fiber to the pretreatment solution is polyvinyl alcohol fiber: pretreatment solution = 8:100; heating in a water bath to 75° C., and then stirring at a constant temperature for 20 minutes, solid-liquid separation, the solid phase is washed 3 times with deionized water, and dried at 60° C. for 1 hour to obtain pretreated fiber;
[0023] (2) preparing a composite N,N-dimethylformamide solution of 2-methyl-2-acrylamide propanesulfonic acid and acrylamide; in the composite N,N-dimethylformamide solution of 2-methyl-2-acrylamide propanesulfonic acid and acrylamide, the mass percentage of 2-methyl-2-acrylamide propanesulfonic acid is 6%, the mass percentage of acrylamide is 0.6%, and the solvent is N,N-dimethylformamide; adding the pretreated fiber to N,N-dimethylformamide in a reaction kettle, the mass ratio of the pretreated fiber to N,N-dimethylformamide is pretreated fiber: N,N-dimethylformamide = 1:30; stirring and dispersing for 20 minutes under an ultrasonic environment to obtain a dispersion; then adding diisopropylbenzene peroxide to the dispersion under stirring, and the addition is completed. The mixture was then heated to 125° C. in a water bath, and after reaching the temperature, the composite N,N-dimethylformamide solution of 2-methyl-2-acrylamide propanesulfonic acid and acrylamide was added under stirring, and the mass ratio of the added mass of the dicumyl peroxide, the composite N,N-dimethylformamide solution of 2-methyl-2-acrylamide propanesulfonic acid and acrylamide to the mass ratio of the pretreated fiber in the dispersion was dicumyl peroxide: composite N,N-dimethylformamide solution of 2-methyl-2-acrylamide propanesulfonic acid and acrylamide: pretreated fiber = 0.1:10:1; after the addition was completed, the reactor was closed, magnetically stirred at a constant temperature of 125° C. for 5 hours, and then naturally cooled to room temperature, the reactor was opened, the solid-liquid separation was carried out, the solid phase was washed 3 times with deionized water, and dried at 60° C. for 1 hour to obtain a primary modified fiber;
[0024] (3) preparing an aqueous solution of ethylenediamine; in the aqueous solution of ethylenediamine, the concentration of ethylenediamine is 10 g / L, and the solvent is water; adding the primary modified fiber to a dilute sodium hydroxide solution, the mass ratio of the primary modified fiber to the dilute sodium hydroxide solution is primary modified fiber: dilute sodium hydroxide solution = 1 g: 50 mL, wherein the concentration of sodium hydroxide in the dilute sodium hydroxide solution is 8 g / L, and the solvent is water; stirring for 10 minutes, and then adding epichlorohydrin to the solution under stirring, the mass ratio of the added epichlorohydrin to the mass of the primary modified fiber in the solution is 8 g / L. Epichlorohydrin: once modified fiber = 4:1; continue stirring for 30 minutes after the addition is completed, then separate the solid and liquid, wash the solid phase with deionized water 3 times, then wash with ethanol 3 times, dry at 60°C for 1 hour, add the dried solid phase to the aqueous solution of ethylenediamine, and the amount ratio of the dried solid phase to the aqueous solution of ethylenediamine is the dried solid phase: the aqueous solution of ethylenediamine = 1g: 30mL; heat to 50°C in a water bath for insulation, then stir for 5 hours, separate the solid and liquid, wash the solid phase with deionized water 3 times, and dry at 60°C for 1 hour to obtain the modified polyvinyl alcohol fiber.
[0025] The preparation method of the modified corn starch is:
[0026] Step 1, preparing an aqueous solution of sodium carbonate, wherein the concentration of sodium carbonate in the aqueous solution of sodium carbonate is 100 g / L, and the solvent is water; then adding corn starch powder to the aqueous solution of sodium carbonate; the amount ratio of corn starch powder added to the aqueous solution of sodium carbonate is corn starch powder: aqueous solution of sodium carbonate = 2 g: 100 mL; after the addition is completed, stirring for 40 minutes, filtering, and drying the filter cake at 50° C. for 10 hours to obtain pretreated starch;
[0027] Step 2: Heat the maleic anhydride in a water bath to 80° C. and keep it warm to melt, then add the pretreated starch, the mixing mass ratio of the pretreated starch and maleic anhydride is pretreated starch: maleic anhydride = 1:5; stir at a constant temperature of 80° C. for 3 hours, filter, wash the filter cake with dichloromethane 3 times, and dry at 50° C. for 10 hours to obtain the modified corn starch.
[0028] The preparation method of the waterproof gypsum board comprises the following steps:
[0029] 1) weighing each component according to the weight proportion, then uniformly mixing the modified polyvinyl alcohol fiber, DL-tartaric acid, sodium trimethyl phosphate, calcium polynaphthalene sulfonate and water, and then adding the remaining desulfurized gypsum powder, modified corn starch and organosilicon waterproofing agent after uniform mixing, and mixing and stirring to obtain slurry;
[0030] 2) Casting the slurry in a mold with front and rear waterproof facing papers, removing the mold after initial setting, drying at 160° C. for 40 min, then drying at 120° C. for 60 min; and then drying at 40° C. for 12 h to obtain the waterproof paper-faced gypsum board.
[0031] Example 2
[0032] A waterproof paper-faced gypsum board based on desulfurized gypsum comprises a board core and a waterproof facing paper, wherein the board core is bonded to the facing paper, and the raw materials of the board core comprise: desulfurized gypsum powder, modified polyvinyl alcohol fiber, modified corn starch, DL-tartaric acid, trimethyl sodium phosphate, silicone waterproofing agent, calcium polynaphthalene sulfonate and water, wherein the raw materials are calculated by weight as follows: 100 parts of desulfurized gypsum powder, 6 parts of modified polyvinyl alcohol fiber, 1 part of modified corn starch, 1 part of DL-tartaric acid, 1 part of trimethyl sodium phosphate, 6 parts of silicone waterproofing agent (methyl high hydrogen silicone oil), 2 parts of calcium polynaphthalene sulfonate and 62 parts of water; wherein the preparation method of the modified polyvinyl alcohol fiber is as follows:
[0033] (1) adding 3-(methacryloyloxy)propyltrimethoxysilane to an aqueous solution of ethanol, wherein the mass ratio of 3-(methacryloyloxy)propyltrimethoxysilane to the aqueous solution of ethanol is 3-(methacryloyloxy)propyltrimethoxysilane: ethanol aqueous solution = 1:100; wherein the mass percentage of ethanol in the aqueous solution of ethanol is 95%, and the rest is water; stirring and mixing for 30 minutes under an ultrasonic environment, and then adding glacial acetic acid to adjust the pH of the solution to 4 to obtain a pretreatment solution; adding polyvinyl alcohol fiber to the pretreatment solution, wherein the mass ratio of polyvinyl alcohol fiber to the pretreatment solution is polyvinyl alcohol fiber: pretreatment solution = 8:100; heating in a water bath to 75° C., and then stirring at a constant temperature for 20 minutes, separating the solid and the liquid, washing the solid phase with deionized water for 3 times, and drying at 60° C. for 1 hour to obtain the pretreated fiber;
[0034] (2) preparing a composite N,N-dimethylformamide solution of 2-methyl-2-acrylamide propanesulfonic acid and acrylamide; in the composite N,N-dimethylformamide solution of 2-methyl-2-acrylamide propanesulfonic acid and acrylamide, the mass percentage of 2-methyl-2-acrylamide propanesulfonic acid is 7%, the mass percentage of acrylamide is 0.8%, and the solvent is N,N-dimethylformamide; adding the pretreated fiber to N,N-dimethylformamide in a reaction kettle, the mass ratio of the pretreated fiber to N,N-dimethylformamide is pretreated fiber: N,N-dimethylformamide = 1:30; stirring and dispersing for 20 minutes under an ultrasonic environment to obtain a dispersion; then adding diisopropylbenzene peroxide to the dispersion under stirring, and the addition is completed. The mixture was then heated to 125° C. in a water bath, and after reaching the temperature, the composite N,N-dimethylformamide solution of 2-methyl-2-acrylamide propanesulfonic acid and acrylamide was added under stirring, and the mass ratio of the added mass of the dicumyl peroxide, the composite N,N-dimethylformamide solution of 2-methyl-2-acrylamide propanesulfonic acid and acrylamide to the mass ratio of the pretreated fiber in the dispersion was dicumyl peroxide: composite N,N-dimethylformamide solution of 2-methyl-2-acrylamide propanesulfonic acid and acrylamide: pretreated fiber = 0.1:12:1; after the addition was completed, the reactor was closed, magnetically stirred at a constant temperature of 125° C. for 5 hours, and then naturally cooled to room temperature, the reactor was opened, the solid-liquid separation was carried out, the solid phase was washed 3 times with deionized water, and dried at 60° C. for 1 hour to obtain a primary modified fiber;
[0035] (3) preparing an aqueous solution of ethylenediamine; in the aqueous solution of ethylenediamine, the concentration of ethylenediamine is 13 g / L, and the solvent is water; adding the primary modified fiber to a dilute sodium hydroxide solution, the mass ratio of the primary modified fiber to the dilute sodium hydroxide solution is primary modified fiber: dilute sodium hydroxide solution = 1 g: 50 mL, wherein the concentration of sodium hydroxide in the dilute sodium hydroxide solution is 9 g / L, and the solvent is water; stirring for 10 minutes, and then adding epichlorohydrin to the solution under stirring, the mass ratio of the added epichlorohydrin to the mass of the primary modified fiber in the solution is Epichlorohydrin: once modified fiber = 5:1; continue stirring for 30 minutes after the addition is completed, then separate the solid and liquid, wash the solid phase with deionized water 3 times, then wash with ethanol 3 times, dry at 60°C for 1 hour, add the dried solid phase to the aqueous solution of ethylenediamine, and the amount ratio of the dried solid phase to the aqueous solution of ethylenediamine is the dried solid phase: the aqueous solution of ethylenediamine = 1g: 30mL; heat to 50°C in a water bath for insulation, then stir for 5 hours, separate the solid and liquid, wash the solid phase with deionized water 3 times, and dry at 60°C for 1 hour to obtain the modified polyvinyl alcohol fiber.
[0036] The preparation method of the modified corn starch is:
[0037] Step 1, preparing an aqueous solution of sodium carbonate, wherein the concentration of sodium carbonate in the aqueous solution of sodium carbonate is 100 g / L, and the solvent is water; then adding corn starch powder to the aqueous solution of sodium carbonate; the amount ratio of corn starch powder added to the aqueous solution of sodium carbonate is corn starch powder: aqueous solution of sodium carbonate = 2 g: 100 mL; after the addition is completed, stirring for 40 minutes, filtering, and drying the filter cake at 50° C. for 10 hours to obtain pretreated starch;
[0038] Step 2: Heat the maleic anhydride in a water bath to 80° C. and keep it warm to melt, then add the pretreated starch, the mixing mass ratio of the pretreated starch and maleic anhydride is pretreated starch: maleic anhydride = 1:5; stir at a constant temperature of 80° C. for 3 hours, filter, wash the filter cake with dichloromethane 3 times, and dry at 50° C. for 10 hours to obtain the modified corn starch.
[0039] The preparation method of the waterproof gypsum board comprises the following steps:
[0040] 1) weighing each component according to the weight proportion, then uniformly mixing the modified polyvinyl alcohol fiber, DL-tartaric acid, sodium trimethyl phosphate, calcium polynaphthalene sulfonate and water, and then adding the remaining desulfurized gypsum powder, modified corn starch and organosilicon waterproofing agent after uniform mixing, and mixing and stirring to obtain slurry;
[0041] 2) Casting the slurry in a mold with front and rear waterproof facing papers, removing the mold after initial setting, drying at 160° C. for 40 min, then drying at 120° C. for 60 min; and then drying at 40° C. for 12 h to obtain the waterproof paper-faced gypsum board.
[0042] Example 3
[0043] A desulfurized gypsum-based waterproof paper-faced gypsum board comprises a board core and a waterproof face paper, wherein the board core is bonded to the face paper, and the raw materials of the board core comprise: desulfurized gypsum powder, modified polyvinyl alcohol fiber, modified corn starch, DL-tartaric acid, trimethyl sodium phosphate, organic silicon waterproofing agent, calcium polynaphthalene sulfonate and water, wherein the raw materials are calculated by weight as follows: 100 parts of desulfurized gypsum powder, 7 parts of modified polyvinyl alcohol fiber, 1.2 parts of modified corn starch, 2 parts of DL-tartaric acid, 2 parts of trimethyl sodium phosphate, 7 parts of organic silicon waterproofing agent (methyl high hydrogen silicone oil), 3 parts of calcium polynaphthalene sulfonate and 64 parts of water; wherein the preparation method of the modified polyvinyl alcohol fiber is as follows:
[0044] (1) adding 3-(methacryloyloxy)propyltrimethoxysilane to an aqueous solution of ethanol, wherein the mass ratio of 3-(methacryloyloxy)propyltrimethoxysilane to the aqueous solution of ethanol is 3-(methacryloyloxy)propyltrimethoxysilane: ethanol aqueous solution = 2:100; wherein the mass percentage of ethanol in the aqueous solution of ethanol is 95%, and the rest is water; stirring and mixing for 30 minutes under an ultrasonic environment, and then adding glacial acetic acid to adjust the pH of the solution to 5 to obtain a pretreatment solution; adding polyvinyl alcohol fiber to the pretreatment solution, wherein the mass ratio of polyvinyl alcohol fiber to the pretreatment solution is polyvinyl alcohol fiber: pretreatment solution = 8:100; heating in a water bath to 75° C., and then stirring at a constant temperature for 20 minutes, separating the solid and the liquid, washing the solid phase with deionized water for 3 times, and drying at 60° C. for 1 hour to obtain the pretreated fiber;
[0045] (2) preparing a composite N,N-dimethylformamide solution of 2-methyl-2-acrylamidopropanesulfonic acid and acrylamide; 液In the composite N,N-dimethylformamide solution of 2-methyl-2-acrylamide propanesulfonic acid and acrylamide, the mass percentage of 2-methyl-2-acrylamide propanesulfonic acid is 7%, the mass percentage of acrylamide is 0.8%, and the solvent is N,N-dimethylformamide; the pretreated fiber is added to N,N-dimethylformamide in a reaction kettle, and the mass ratio of the pretreated fiber to N,N-dimethylformamide is pretreated fiber: N,N-dimethylformamide = 1:30; stirring and dispersing for 20 minutes under ultrasonic environment to obtain a dispersion; then adding diisopropylbenzene peroxide to the dispersion under stirring, heating to 125° C. in a water bath after the addition is completed, and stirring under stirring after reaching the temperature The composite N,N-dimethylformamide solution of 2-methyl-2-acrylamide propanesulfonic acid and acrylamide is added, and the mass ratio of the added mass of the diisopropylbenzene peroxide, the composite N,N-dimethylformamide solution of 2-methyl-2-acrylamide propanesulfonic acid and acrylamide to the mass ratio of the pretreated fiber in the dispersion is diisopropylbenzene peroxide: composite N,N-dimethylformamide solution of 2-methyl-2-acrylamide propanesulfonic acid and acrylamide: pretreated fiber = 0.2:14:1; after the addition is completed, the reactor is closed, magnetically stirred at a constant temperature of 125° C. for 5 hours, and then naturally cooled to room temperature, the reactor is opened, the solid-liquid separation is carried out, the solid phase is washed 3 times with deionized water, and dried at 60° C. for 1 hour to obtain a primary modified fiber;
[0046] (3) preparing an aqueous solution of ethylenediamine; in the aqueous solution of ethylenediamine, the concentration of ethylenediamine is 13 g / L, and the solvent is water; adding the primary modified fiber to a dilute sodium hydroxide solution, the mass ratio of the primary modified fiber to the dilute sodium hydroxide solution is primary modified fiber: dilute sodium hydroxide solution = 1 g: 50 mL, wherein the concentration of sodium hydroxide in the dilute sodium hydroxide solution is 9 g / L, and the solvent is water; stirring for 10 minutes, and then adding epichlorohydrin to the solution under stirring, the mass ratio of the added epichlorohydrin to the mass of the primary modified fiber in the solution is Epichlorohydrin: once modified fiber = 5:1; continue stirring for 30 minutes after the addition is completed, then separate the solid and liquid, wash the solid phase with deionized water 3 times, then wash with ethanol 3 times, dry at 60°C for 1 hour, add the dried solid phase to the aqueous solution of ethylenediamine, and the amount ratio of the dried solid phase to the aqueous solution of ethylenediamine is the dried solid phase: the aqueous solution of ethylenediamine = 1g: 30mL; heat to 50°C in a water bath for insulation, then stir for 5 hours, separate the solid and liquid, wash the solid phase with deionized water 3 times, and dry at 60°C for 1 hour to obtain the modified polyvinyl alcohol fiber.
[0047] The preparation method of the modified corn starch is:
[0048] Step 1, preparing an aqueous solution of sodium carbonate, wherein the concentration of sodium carbonate in the aqueous solution of sodium carbonate is 100 g / L, and the solvent is water; then adding corn starch powder to the aqueous solution of sodium carbonate; the amount ratio of corn starch powder added to the aqueous solution of sodium carbonate is corn starch powder: aqueous solution of sodium carbonate = 2 g: 100 mL; after the addition is completed, stirring for 40 minutes, filtering, and drying the filter cake at 50° C. for 10 hours to obtain pretreated starch;
[0049] Step 2: Heat the maleic anhydride in a water bath to 80° C. and keep it warm to melt, then add the pretreated starch, the mixing mass ratio of the pretreated starch and maleic anhydride is pretreated starch: maleic anhydride = 1:5; stir at a constant temperature of 80° C. for 3 hours, filter, wash the filter cake with dichloromethane 3 times, and dry at 50° C. for 10 hours to obtain the modified corn starch.
[0050] The preparation method of the waterproof gypsum board comprises the following steps:
[0051] 1) weighing each component according to the weight proportion, then uniformly mixing the modified polyvinyl alcohol fiber, DL-tartaric acid, sodium trimethyl phosphate, calcium polynaphthalene sulfonate and water, and then adding the remaining desulfurized gypsum powder, modified corn starch and organosilicon waterproofing agent after uniform mixing, and mixing and stirring to obtain slurry;
[0052] 2) Casting the slurry in a mold with front and rear waterproof facing papers, removing the mold after initial setting, drying at 160° C. for 40 min, then drying at 120° C. for 60 min; and then drying at 40° C. for 12 h to obtain the waterproof paper-faced gypsum board.
[0053] Example 4
[0054] A waterproof paper-faced gypsum board based on desulfurized gypsum comprises a board core and a waterproof facing paper, wherein the board core is bonded to the facing paper, and the raw materials of the board core comprise: desulfurized gypsum powder, modified polyvinyl alcohol fiber, modified corn starch, DL-tartaric acid, trimethyl sodium phosphate, organic silicon waterproofing agent, calcium polynaphthalene sulfonate and water, wherein the raw materials are calculated by weight as follows: 100 parts of desulfurized gypsum powder, 8 parts of modified polyvinyl alcohol fiber, 1.5 parts of modified corn starch, 2 parts of DL-tartaric acid, 2 parts of trimethyl sodium phosphate, 8 parts of organic silicon waterproofing agent (methyl high hydrogen silicone oil), 4 parts of calcium polynaphthalene sulfonate and 65 parts of water; wherein the preparation method of the modified polyvinyl alcohol fiber is as follows:
[0055] (1) adding 3-(methacryloyloxy)propyltrimethoxysilane to an aqueous solution of ethanol, wherein the mass ratio of 3-(methacryloyloxy)propyltrimethoxysilane to the aqueous solution of ethanol is 3-(methacryloyloxy)propyltrimethoxysilane: ethanol aqueous solution = 2:100; wherein the mass percentage of ethanol in the aqueous solution of ethanol is 95%, and the rest is water; stirring and mixing for 30 minutes under an ultrasonic environment, and then adding glacial acetic acid to adjust the pH of the solution to 5 to obtain a pretreatment solution; adding polyvinyl alcohol fiber to the pretreatment solution, wherein the mass ratio of polyvinyl alcohol fiber to the pretreatment solution is polyvinyl alcohol fiber: pretreatment solution = 8:100; heating in a water bath to 75° C., and then stirring at a constant temperature for 20 minutes, separating the solid and the liquid, washing the solid phase with deionized water for 3 times, and drying at 60° C. for 1 hour to obtain the pretreated fiber;
[0056] (2) preparing a composite N,N-dimethylformamide solution of 2-methyl-2-acrylamide propanesulfonic acid and acrylamide; in the composite N,N-dimethylformamide solution of 2-methyl-2-acrylamide propanesulfonic acid and acrylamide, the mass percentage of 2-methyl-2-acrylamide propanesulfonic acid is 8%, the mass percentage of acrylamide is 1%, and the solvent is N,N-dimethylformamide; adding the pretreated fiber to N,N-dimethylformamide in a reaction kettle, the mass ratio of the pretreated fiber to N,N-dimethylformamide is pretreated fiber: N,N-dimethylformamide = 1:30; stirring and dispersing under ultrasonic environment for 20 minutes to obtain a dispersion; then adding diisopropylbenzene peroxide to the dispersion under stirring, after the addition is completed The method comprises the following steps: heating the mixture in a water bath to 125° C., adding the composite N,N-dimethylformamide solution of 2-methyl-2-acrylamide propanesulfonic acid and acrylamide under stirring after the mixture reaches the temperature, wherein the mass ratio of the added dicumyl peroxide, the composite N,N-dimethylformamide solution of 2-methyl-2-acrylamide propanesulfonic acid and acrylamide to the mass ratio of the added mass of the pretreated fiber in the dispersion is dicumyl peroxide: composite N,N-dimethylformamide solution of 2-methyl-2-acrylamide propanesulfonic acid and acrylamide: pretreated fiber = 0.2:15:1; after the addition is completed, the reaction kettle is closed, magnetically stirred at a constant temperature of 125° C. for 5 hours, and then naturally cooled to room temperature, the reaction kettle is opened, the solid-liquid separation is carried out, the solid phase is washed with deionized water for 3 times, and dried at 60° C. for 1 hour to obtain a primary modified fiber;
[0057] (3) preparing an aqueous solution of ethylenediamine; in the aqueous solution of ethylenediamine, the concentration of ethylenediamine is 15 g / L, and the solvent is water; adding the primary modified fiber to a dilute sodium hydroxide solution, the mass ratio of the primary modified fiber to the dilute sodium hydroxide solution is primary modified fiber: dilute sodium hydroxide solution = 1 g: 50 mL, wherein the concentration of sodium hydroxide in the dilute sodium hydroxide solution is 10 g / L, and the solvent is water; stirring for 10 minutes, and then adding epichlorohydrin to the solution under stirring, the mass ratio of the added epichlorohydrin to the mass of the primary modified fiber in the solution is 1:1. The ratio of epichlorohydrin to modified fiber is 6:1; after the addition is completed, stirring is continued for 30 minutes, then the solid-liquid separation is carried out, the solid phase is washed with deionized water for 3 times, and then washed with ethanol for 3 times, and dried at 60°C for 1 hour, and the dried solid phase is added to the aqueous solution of ethylenediamine, and the amount ratio of the dried solid phase to the aqueous solution of ethylenediamine is the dried solid phase: the aqueous solution of ethylenediamine = 1g: 30mL; heating to 50°C in a water bath for insulation, and then stirring for 5 hours, solid-liquid separation is carried out, the solid phase is washed with deionized water for 3 times, and dried at 60°C for 1 hour to obtain the modified polyvinyl alcohol fiber.
[0058] The preparation method of the modified corn starch is:
[0059] Step 1, preparing an aqueous solution of sodium carbonate, wherein the concentration of sodium carbonate in the aqueous solution of sodium carbonate is 100 g / L, and the solvent is water; then adding corn starch powder to the aqueous solution of sodium carbonate; the amount ratio of corn starch powder added to the aqueous solution of sodium carbonate is corn starch powder: aqueous solution of sodium carbonate = 2 g: 100 mL; after the addition is completed, stirring for 40 minutes, filtering, and drying the filter cake at 50° C. for 10 hours to obtain pretreated starch;
[0060] Step 2: Heat the maleic anhydride in a water bath to 80° C. and keep it warm to melt, then add the pretreated starch, the mixing mass ratio of the pretreated starch and maleic anhydride is pretreated starch: maleic anhydride = 1:5; stir at a constant temperature of 80° C. for 3 hours, filter, wash the filter cake with dichloromethane 3 times, and dry at 50° C. for 10 hours to obtain the modified corn starch.
[0061] The preparation method of the waterproof gypsum board comprises the following steps:
[0062] 1) weighing each component according to the weight proportion, then uniformly mixing the modified polyvinyl alcohol fiber, DL-tartaric acid, sodium trimethyl phosphate, calcium polynaphthalene sulfonate and water, and then adding the remaining desulfurized gypsum powder, modified corn starch and organosilicon waterproofing agent after uniform mixing, and mixing and stirring to obtain slurry;
[0063] 2) Casting the slurry in a mold with front and rear waterproof facing papers, removing the mold after initial setting, drying at 160° C. for 40 min, then drying at 120° C. for 60 min; and then drying at 40° C. for 12 h to obtain the waterproof paper-faced gypsum board.
[0064] Comparative Example 1
[0065] A waterproof paper-faced gypsum board for comparison comprises a board core and a waterproof facing paper, wherein the board core is bonded to the facing paper, and the raw materials of the board core comprise: desulfurized gypsum powder, polyvinyl alcohol fiber, modified corn starch, DL-tartaric acid, trimethyl sodium phosphate, organosilicon waterproofing agent, calcium polynaphthalene sulfonate and water, wherein the raw materials are calculated by weight as follows: 100 parts of desulfurized gypsum powder, 6 parts of polyvinyl alcohol fiber, 1 part of modified corn starch, 1 part of DL-tartaric acid, 1 part of trimethyl sodium phosphate, 6 parts of organosilicon waterproofing agent (methyl high hydrogen silicone oil), 2 parts of calcium polynaphthalene sulfonate and 62 parts of water;
[0066] The preparation method of the modified corn starch is:
[0067] Step 1, preparing an aqueous solution of sodium carbonate, wherein the concentration of sodium carbonate in the aqueous solution of sodium carbonate is 100 g / L, and the solvent is water; then adding corn starch powder to the aqueous solution of sodium carbonate; the amount ratio of corn starch powder added to the aqueous solution of sodium carbonate is corn starch powder: aqueous solution of sodium carbonate = 2 g: 100 mL; after the addition is completed, stirring for 40 minutes, filtering, and drying the filter cake at 50° C. for 10 hours to obtain pretreated starch;
[0068] Step 2: Heat the maleic anhydride in a water bath to 80° C. and keep it warm to melt, then add the pretreated starch, the mixing mass ratio of the pretreated starch and maleic anhydride is pretreated starch: maleic anhydride = 1:5; stir at a constant temperature of 80° C. for 3 hours, filter, wash the filter cake with dichloromethane 3 times, and dry at 50° C. for 10 hours to obtain the modified corn starch.
[0069] The preparation method of the waterproof gypsum board comprises the following steps:
[0070] 1) weighing each component according to the weight proportion, then uniformly mixing the polyvinyl alcohol fiber, DL-tartaric acid, sodium trimethyl phosphate, calcium polynaphthalene sulfonate and water, and then adding the remaining desulfurized gypsum powder, modified corn starch and organosilicon waterproofing agent after uniform mixing, and mixing and stirring to obtain a slurry;
[0071] 2) Cast the slurry in a mold with front and rear waterproof facing papers, remove the mold after initial setting, dry at 160°C for 40 minutes, then dry at 120°C for 60 minutes; and then dry at 40°C for 12 hours to obtain the waterproof paper-faced gypsum board described in this comparative example.
[0072] Comparative Example 2
[0073] A comparative waterproof paper-faced gypsum board comprises a board core and a waterproof facing paper, wherein the board core is bonded to the facing paper, and the raw materials of the board core comprise: desulfurized gypsum powder, modified polyvinyl alcohol fiber, modified corn starch, DL-tartaric acid, trimethyl sodium phosphate, silicone waterproofing agent, calcium polynaphthalene sulfonate and water, wherein the raw materials are calculated by weight as follows: 100 parts of desulfurized gypsum powder, 6 parts of modified polyvinyl alcohol fiber, 1 part of modified corn starch, 1 part of DL-tartaric acid, 1 part of trimethyl sodium phosphate, 6 parts of silicone waterproofing agent (methyl high hydrogen silicone oil), 2 parts of calcium polynaphthalene sulfonate, and 62 parts of water; wherein the preparation method of the modified polyvinyl alcohol fiber is as follows:
[0074] (1) adding 3-(methacryloyloxy)propyltrimethoxysilane to an aqueous solution of ethanol, wherein the mass ratio of 3-(methacryloyloxy)propyltrimethoxysilane to the aqueous solution of ethanol is 3-(methacryloyloxy)propyltrimethoxysilane: ethanol aqueous solution = 1:100; wherein the mass percentage of ethanol in the aqueous solution of ethanol is 95%, and the rest is water; stirring and mixing for 30 minutes under an ultrasonic environment, and then adding glacial acetic acid to adjust the pH of the solution to 4 to obtain a pretreatment solution; adding polyvinyl alcohol fiber to the pretreatment solution, wherein the mass ratio of polyvinyl alcohol fiber to the pretreatment solution is polyvinyl alcohol fiber: pretreatment solution = 8:100; heating in a water bath to 75° C., and then stirring at a constant temperature for 20 minutes, separating the solid and the liquid, washing the solid phase with deionized water for 3 times, and drying at 60° C. for 1 hour to obtain the pretreated fiber;
[0075] (2) preparing a composite N,N-dimethylformamide solution of 2-methyl-2-acrylamide propanesulfonic acid and acrylamide; in the composite N,N-dimethylformamide solution of 2-methyl-2-acrylamide propanesulfonic acid and acrylamide, the mass percentage of 2-methyl-2-acrylamide propanesulfonic acid is 7%, the mass percentage of acrylamide is 0.8%, and the solvent is N,N-dimethylformamide; adding the pretreated fiber to N,N-dimethylformamide in a reaction kettle, the mass ratio of the pretreated fiber to N,N-dimethylformamide is pretreated fiber: N,N-dimethylformamide = 1:30; stirring and dispersing under ultrasonic environment for 20 minutes to obtain a dispersion; then adding diisopropylbenzene peroxide to the dispersion under stirring, and heating in a water bath after the addition is completed. Heat to 125° C., and then add the composite N,N-dimethylformamide solution of 2-methyl-2-acrylamide propanesulfonic acid and acrylamide under stirring after reaching temperature, the mass ratio of the added dicumyl peroxide, the composite N,N-dimethylformamide solution of 2-methyl-2-acrylamide propanesulfonic acid and acrylamide to the mass ratio of the pretreated fiber in the dispersion is dicumyl peroxide: composite N,N-dimethylformamide solution of 2-methyl-2-acrylamide propanesulfonic acid and acrylamide: pretreated fiber = 0.1:12:1; after the addition is completed, close the reactor, stir magnetically at a constant temperature of 125° C. for 5 hours, then cool naturally to room temperature, open the reactor, separate the solid and liquid, wash the solid phase with deionized water 3 times, and dry at 60° C. for 1 hour to obtain the modified polyvinyl alcohol fiber described in this comparative example.
[0076] The preparation method of the modified corn starch is:
[0077] Step 1, preparing an aqueous solution of sodium carbonate, wherein the concentration of sodium carbonate in the aqueous solution of sodium carbonate is 100 g / L, and the solvent is water; then adding corn starch powder to the aqueous solution of sodium carbonate; the amount ratio of corn starch powder added to the aqueous solution of sodium carbonate is corn starch powder: aqueous solution of sodium carbonate = 2 g: 100 mL; after the addition is completed, stirring for 40 minutes, filtering, and drying the filter cake at 50° C. for 10 hours to obtain pretreated starch;
[0078] Step 2: Heat the maleic anhydride in a water bath to 80° C. and keep it warm to melt, then add the pretreated starch, the mixing mass ratio of the pretreated starch and maleic anhydride is pretreated starch: maleic anhydride = 1:5; stir at a constant temperature of 80° C. for 3 hours, filter, wash the filter cake with dichloromethane 3 times, and dry at 50° C. for 10 hours to obtain the modified corn starch.
[0079] The preparation method of the waterproof gypsum board comprises the following steps:
[0080] 1) weighing each component according to the weight proportion, then uniformly mixing the modified polyvinyl alcohol fiber, DL-tartaric acid, sodium trimethyl phosphate, calcium polynaphthalene sulfonate and water, and then adding the remaining desulfurized gypsum powder, modified corn starch and organosilicon waterproofing agent after uniform mixing, and mixing and stirring to obtain slurry;
[0081] 2) Cast the slurry in a mold with front and rear waterproof facing papers, remove the mold after initial setting, dry at 160°C for 40 minutes, then dry at 120°C for 60 minutes; and then dry at 40°C for 12 hours to obtain the waterproof paper-faced gypsum board described in this comparative example.
[0082] Comparative Example 3
[0083] A comparative waterproof paper-faced gypsum board comprises a board core and a waterproof facing paper, wherein the board core is bonded to the facing paper, and the raw materials of the board core comprise: desulfurized gypsum powder, modified polyvinyl alcohol fiber, modified corn starch, DL-tartaric acid, trimethyl sodium phosphate, silicone waterproofing agent, calcium polynaphthalene sulfonate and water, wherein the raw materials are calculated by weight as follows: 100 parts of desulfurized gypsum powder, 6 parts of modified polyvinyl alcohol fiber, 1 part of modified corn starch, 1 part of DL-tartaric acid, 1 part of trimethyl sodium phosphate, 6 parts of silicone waterproofing agent (methyl high hydrogen silicone oil), 2 parts of calcium polynaphthalene sulfonate, and 62 parts of water; wherein the preparation method of the modified polyvinyl alcohol fiber is as follows:
[0084] (1) adding 3-(methacryloyloxy)propyltrimethoxysilane to an aqueous solution of ethanol, wherein the mass ratio of 3-(methacryloyloxy)propyltrimethoxysilane to the aqueous solution of ethanol is 3-(methacryloyloxy)propyltrimethoxysilane: ethanol aqueous solution = 1:100; wherein the mass percentage of ethanol in the aqueous solution of ethanol is 95%, and the rest is water; stirring and mixing for 30 minutes under an ultrasonic environment, and then adding glacial acetic acid to adjust the pH of the solution to 4 to obtain a pretreatment solution; adding polyvinyl alcohol fiber to the pretreatment solution, wherein the mass ratio of polyvinyl alcohol fiber to the pretreatment solution is polyvinyl alcohol fiber: pretreatment solution = 8:100; heating in a water bath to 75° C., and then stirring at a constant temperature for 20 minutes, separating the solid and the liquid, washing the solid phase with deionized water for 3 times, and drying at 60° C. for 1 hour to obtain the pretreated fiber;
[0085] (2) preparing an aqueous solution of ethylenediamine; in the aqueous solution of ethylenediamine, the concentration of ethylenediamine is 13 g / L, and the solvent is water; adding the pretreated fiber to a dilute sodium hydroxide solution, the amount ratio of the pretreated fiber to the dilute sodium hydroxide solution is pretreated fiber: dilute sodium hydroxide solution = 1 g: 50 mL, wherein the concentration of sodium hydroxide in the dilute sodium hydroxide solution is 9 g / L, and the solvent is water; stirring for 10 min, and then adding epichlorohydrin to the solution under stirring, the mass ratio of the added epichlorohydrin to the mass of the pretreated fiber in the solution is 1:1. Propane: pretreated fiber = 5:1; continue stirring for 30 minutes after the addition is completed, then separate the solid and liquid, wash the solid phase with deionized water 3 times, then wash with ethanol 3 times, and dry at 60°C for 1 hour, and add the dried solid phase to the aqueous solution of ethylenediamine, and the amount ratio of the dried solid phase to the aqueous solution of ethylenediamine is the dried solid phase: the aqueous solution of ethylenediamine = 1g: 30mL; heat in a water bath to 50°C for insulation, then stir for 5 hours, separate the solid and liquid, wash the solid phase with deionized water 3 times, and dry at 60°C for 1 hour to obtain the modified polyvinyl alcohol fiber described in this comparative example.
[0086] The preparation method of the modified corn starch is:
[0087] Step 1, preparing an aqueous solution of sodium carbonate, wherein the concentration of sodium carbonate in the aqueous solution of sodium carbonate is 100 g / L, and the solvent is water; then adding corn starch powder to the aqueous solution of sodium carbonate; the amount ratio of corn starch powder added to the aqueous solution of sodium carbonate is corn starch powder: aqueous solution of sodium carbonate = 2 g: 100 mL; after the addition is completed, stirring for 40 minutes, filtering, and drying the filter cake at 50° C. for 10 hours to obtain pretreated starch;
[0088] Step 2: Heat the maleic anhydride in a water bath to 80° C. and keep it warm to melt, then add the pretreated starch, the mixing mass ratio of the pretreated starch and maleic anhydride is pretreated starch: maleic anhydride = 1:5; stir at a constant temperature of 80° C. for 3 hours, filter, wash the filter cake with dichloromethane 3 times, and dry at 50° C. for 10 hours to obtain the modified corn starch.
[0089] The preparation method of the waterproof gypsum board comprises the following steps:
[0090] 1) weighing each component according to the weight proportion, then uniformly mixing the modified polyvinyl alcohol fiber, DL-tartaric acid, sodium trimethyl phosphate, calcium polynaphthalene sulfonate and water, and then adding the remaining desulfurized gypsum powder, modified corn starch and organosilicon waterproofing agent after uniform mixing, and mixing and stirring to obtain slurry;
[0091] 2) Cast the slurry in a mold with front and rear waterproof facing papers, remove the mold after initial setting, dry at 160°C for 40 minutes, then dry at 120°C for 60 minutes; and then dry at 40°C for 12 hours to obtain the waterproof paper-faced gypsum board described in this comparative example.
[0092] Example 5
[0093] The breaking load and water absorption rate of the waterproof gypsum boards prepared by the methods described in the above embodiments and comparative examples were tested according to the requirements of standard GB / T 9775-2008. The thickness of the boards was 9.5 mm. The results are shown in Table 1.
[0094] As shown in Table 1, the gypsum board prepared by the method of the present invention has good mechanical strength and low water absorption, and can well meet the standard requirements. Comparative Example 2 and the comparative examples show that by using the modification process of the present invention on the polyvinyl alcohol fiber, the strength of the gypsum board can be significantly improved and the water absorption can be improved. This is mainly due to: firstly, alkylation treatment is performed on the surface of the polyvinyl alcohol fiber, and then acrylamide groups are grafted to improve the dispersion of the fiber and the compatibility of the fiber with gypsum, reduce the pores between the phases, and improve the density; then the fiber surface is aminoated and maleic anhydride modified starch is used to make the binding force between the modified fiber and the modified starch stronger, thereby improving the overall strength of the material.
[0095]
[0096] The technical solution provided by the present invention is introduced in detail above. For those skilled in the art, according to the concept of the embodiments of the present invention, there may be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as limiting the present invention.
Claims
1. A waterproof gypsum board based on desulfurized gypsum, characterized in that: The invention comprises a board core and a waterproof face paper, wherein the board core is bonded to the face paper, and the raw materials of the board core include: desulfurized gypsum powder, modified polyvinyl alcohol fiber, modified corn starch, DL-tartaric acid, trimethyl sodium phosphate, silicone waterproofing agent, calcium polynaphthalene sulfonate and water, wherein the preparation method of the modified polyvinyl alcohol fiber is: (1) adding 3-(methacryloyloxy)propyltrimethoxysilane to an aqueous solution of ethanol, stirring and mixing under an ultrasonic environment for more than 30 minutes, and then adding glacial acetic acid to adjust the pH of the solution to 4-5 to obtain a pretreatment solution; adding polyvinyl alcohol fiber to the pretreatment solution, heating it to 75±5° C. in a water bath, and then stirring it at a constant temperature for more than 20 minutes, separating the solid and the liquid, washing the solid phase with deionized water for more than 3 times, and drying it at 60° C. for more than 1 hour to obtain a pretreated fiber; (2) preparing a composite N,N-dimethylformamide solution of 2-methyl-2-acrylamide propanesulfonic acid and acrylamide; adding the pretreated fiber to N,N-dimethylformamide in a reactor, stirring and dispersing for more than 20 minutes under an ultrasonic environment to obtain a dispersion; then adding diisopropylbenzene peroxide to the dispersion under stirring, heating the dispersion to 125±3° C. in a water bath after the addition is completed, and then adding the composite N,N-dimethylformamide solution of 2-methyl-2-acrylamide propanesulfonic acid and acrylamide under stirring after the addition is completed, closing the reactor after the addition is completed, magnetically stirring at a constant temperature of 125±3° C. for more than 5 hours, and then naturally cooling to room temperature, opening the reactor, separating the solid and the liquid, washing the solid phase with deionized water for more than 3 times, and drying at 60° C. for more than 1 hour to obtain a primary modified fiber; (3) preparing an aqueous solution of ethylenediamine; adding the once modified fiber to a dilute sodium hydroxide solution, stirring for 10 to 15 minutes, then adding epichlorohydrin to the solution under stirring, continuing to stir for more than 30 minutes after the addition is completed, then separating the solid from the liquid, washing the solid phase with deionized water for more than 3 times, then washing with ethanol for more than 3 times, drying at 60°C for more than 1 hour, adding the dried solid phase to the aqueous solution of ethylenediamine, heating to 50±5°C in a water bath, then stirring for more than 5 hours, separating the solid from the liquid, washing the solid phase with deionized water for more than 3 times, and drying at 60°C for more than 1 hour, and obtaining the modified polyvinyl alcohol fiber.
2. A waterproof gypsum board based on desulfurized gypsum according to claim 1, characterized in that: The preparation method of the modified corn starch is: Step 1, preparing an aqueous solution of sodium carbonate, wherein the concentration of sodium carbonate in the aqueous solution of sodium carbonate is 100 g / L, and the solvent is water; then adding corn starch powder to the aqueous solution of sodium carbonate; the amount ratio of corn starch powder added to the aqueous solution of sodium carbonate is corn starch powder: aqueous solution of sodium carbonate = 2 g: 100 mL; after the addition is completed, stirring for 40 to 50 minutes, filtering, and drying the filter cake at 50° C. for more than 10 hours to obtain pretreated starch; Step 2: Heat the maleic anhydride in a water bath to 80±3°C to keep it melted, then add the pretreated starch, the mixing mass ratio of the pretreated starch and maleic anhydride is pretreated starch: maleic anhydride = 1:5; stir at a constant temperature of 80±3°C for more than 3h, filter, wash the filter cake with dichloromethane for more than 3 times, and dry at 50°C for more than 10h to obtain the modified corn starch.
3. A waterproof gypsum board based on desulfurized gypsum according to claim 1, characterized in that: The raw materials of the board core are calculated by weight as follows: 100 parts of desulfurized gypsum powder, 5-8 parts of modified polyvinyl alcohol fiber, 0.8-1.5 parts of modified corn starch, 1-2 parts of DL-tartaric acid, 1-2 parts of trimethyl sodium phosphate, 5-8 parts of silicone waterproofing agent, 1-4 parts of calcium polynaphthalene sulfonate, and 60-65 parts of water.
4. The waterproof gypsum board based on desulfurized gypsum according to claim 1, characterized in that: The organosilicon waterproofing agent is methyl high hydrogen silicone oil.
5. The waterproof gypsum board based on desulfurized gypsum according to claim 1, characterized in that: In the step (1), the mass ratio of 3-(methacryloyloxy)propyltrimethoxysilane added to the aqueous solution of ethanol is 3-(methacryloyloxy)propyltrimethoxysilane: ethanol aqueous solution = 1-2:100; wherein the mass percentage of ethanol in the aqueous solution of ethanol is 95%, and the rest is water; the mass ratio of polyvinyl alcohol fiber added to the pretreatment solution is polyvinyl alcohol fiber: pretreatment solution = 8-10:
100.
6. The waterproof gypsum board based on desulfurized gypsum according to claim 1, characterized in that: In the step (2), in the composite N,N-dimethylformamide solution of 2-methyl-2-acrylamidepropanesulfonic acid and acrylamide, the mass percentage of 2-methyl-2-acrylamidepropanesulfonic acid is 6% to 8%, the mass percentage of acrylamide is 0.6% to 1%, and the solvent is N,N-dimethylformamide; the mass ratio of the pretreated fiber added to N,N-dimethylformamide is pretreated fiber:N,N-dimethylformamide=1:30; the mass ratio of the added mass of the composite N,N-dimethylformamide solution of dicumyl peroxide, 2-methyl-2-acrylamidepropanesulfonic acid and acrylamide to the mass ratio of the pretreated fiber in the dispersion is dicumyl peroxide: composite N,N-dimethylformamide solution of 2-methyl-2-acrylamidepropanesulfonic acid and acrylamide: pretreated fiber=0.1-0.2:10-15:
1.
7. The waterproof gypsum board based on desulfurized gypsum according to claim 1, characterized in that: In the step (3), the concentration of ethylenediamine in the aqueous solution of ethylenediamine is 10-15 g / L, and the solvent is water; the primary modified fiber is added to the dilute sodium hydroxide solution in a ratio of primary modified fiber: dilute sodium hydroxide solution = 1 g: 50 mL, wherein the concentration of sodium hydroxide in the dilute sodium hydroxide solution is 8-10 g / L, and the solvent is water; the mass ratio of the added epichlorohydrin to the mass of the primary modified fiber in the solution is epichlorohydrin: primary modified fiber = 4-6:1; the amount ratio of the dried solid phase to the aqueous solution of ethylenediamine is the dried solid phase: aqueous solution of ethylenediamine = 1 g: 30 mL.
8. The method for preparing the waterproof gypsum board according to claim 3, characterized in that: The steps are: 1) weighing each component according to the weight proportion, then uniformly mixing the modified polyvinyl alcohol fiber, DL-tartaric acid, sodium trimethyl phosphate, calcium polynaphthalene sulfonate and water, and then adding the remaining desulfurized gypsum powder, modified corn starch and organosilicon waterproofing agent after uniform mixing, and mixing and stirring to obtain slurry; 2) Casting the slurry in a mold with front and rear waterproof facing papers, removing the mold after initial setting, drying at 160-170° C. for 30-40 min, then drying at 110-130° C. for 60-80 min; and then drying at 40-50° C. for more than 12 h to obtain the waterproof paper-faced gypsum board.